Acute effects of dietary phosphorus intake on markers of mineral metabolism in hemodialysis patients: post hoc analysis of a randomized crossover trial. Issue 1 (1st January 2021) - Tsai, Wan-Chuan; Wu, Hon-Yen; Chiu, Yen-Ling; Yang, Ju-Yeh; Pai, Mei-Fen; Wu, Yong-Ru; Lin, Wan-Yu; Hung, Kuan-Yu; Chien, Kuo-Liong; Hsu, Shih-Ping; Peng, Yu-Sen
Abstract: Background: Long-term dietary phosphorus excess influences disturbances in mineral metabolism, but it is unclear how rapidly the mineral metabolism responds to short-term dietary change in dialysis populations. Methods: This was a post hoc analysis of a randomized crossover trial that evaluated the short-term effects of low-phosphorus diets on mineral parameters in hemodialysis patients. Within a 9-day period, we obtained a total of 4 repeated measurements for each participant regarding dietary intake parameters, including calorie, phosphorus, and calcium intake, and markers of mineral metabolism, including phosphate, calcium, intact parathyroid hormone (iPTH), intact fibroblast growth factor 23 (iFGF23), and C-terminal fibroblast growth factor 23 (cFGF23). The correlations between dietary phosphorus intake and serum mineral parameters were assessed by using mixed-effects models. Results: Thirty-four patients were analyzed. In the fully adjusted model, we found that an increase in dietary phosphorus intake of 100 mg was associated with an increase in serum phosphate of 0.3 mg/dL (95% confidence intervals [CI], 0.2–0.4, p < .001), a decrease in serum calcium of 0.06 mg/dL (95% CI, −0.11 to −0.01, p = .01), an increase in iPTH of 5.4% (95% CI, 1.4–9.3, p = .01), and an increase in iFGF23 of 5.0% (95% CI, 2.0–8.0, p = .001). Dietary phosphorus intake was not related to cFGF23. Conclusions: Increased dietary phosphorus intake acutely increases serum phosphate, iPTH, and iFGF23 levels and decreases serum calcium levels, highlighting the important role of daily fluctuations of dietary habits in disturbed mineral homeostasis in hemodialysis patients.